2006
DOI: 10.1002/cphc.200600098
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Edge Plane Sites Slow the Electron Transfer of the Ferro‐/Ferricyanide Redox Couple at Graphite Electrodes

Abstract: The electron transfer kinetics of ferrocyanide, potassium hexachloroiridate(III), hexaammineruthenium(III) chloride, and N,N,N',N'-tetramethyl-p-phenylenediamine (TMPD) have been examined at basal plane and edge plane pyrolytic graphite electrodes which have been allowed to oxidise in air for various periods of time. It is demonstrated via voltammetric and X-ray photoelectron spectroscopy (XPS) analysis that oxygenated species formed at edge plane sites/defects decrease the electron transfer kinetics of ferroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
193
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(210 citation statements)
references
References 18 publications
15
193
0
2
Order By: Relevance
“…Such values range from 10 −6 to 10 2 cm s −1 going from different carbons to metalbased electrodes. [26,[29][30][31][32] As also found in the case of BDD electrodes, the lower values of app 0 k of the Tidoped diamond electrode with respect to metal systems can be ascribed to semiconductive electronic proper ties of the diamond material that translate into a lower poten tialdependent density of electronic states and carrier density as compared to metals. [31,33] Moreover, the absence of specific functional groups on the diamond surface can be responsible for a further rate decrease since it was evidenced that some of them can be involved in the electrocatalysis process of inner sphere electron transfers, such the one occurring for Fe 2+/3+ couple.…”
Section: Cyclic Voltammetrymentioning
confidence: 54%
“…Such values range from 10 −6 to 10 2 cm s −1 going from different carbons to metalbased electrodes. [26,[29][30][31][32] As also found in the case of BDD electrodes, the lower values of app 0 k of the Tidoped diamond electrode with respect to metal systems can be ascribed to semiconductive electronic proper ties of the diamond material that translate into a lower poten tialdependent density of electronic states and carrier density as compared to metals. [31,33] Moreover, the absence of specific functional groups on the diamond surface can be responsible for a further rate decrease since it was evidenced that some of them can be involved in the electrocatalysis process of inner sphere electron transfers, such the one occurring for Fe 2+/3+ couple.…”
Section: Cyclic Voltammetrymentioning
confidence: 54%
“…In the work of Taniguchi and co-workers, the HOPG surface was peeled off with adhesive tape to adsorb fructose dehydrogenase on a fresh basal-plane. 199 The rate of ET for the ferro/ ferricyanide redox couple is much faster at edge-plane graphite than at basal-plane graphite; 200 this can be used to test the nature of the electrode surface and the presence of edge-plane defects. 114 Glassycarbonwasalsoused,althoughlessfrequently.…”
Section: Attaching the Enzymementioning
confidence: 99%
“…[58][59][60][61] There is evidence, for example, that the favorable electrochemical properties of SWNT-modified electrodes arise from oxygenated carbon species, especially carboxyl moieties, which are produced on the tips of the nanotubes during acid purification. [40,50,62] Conversely, other work has found that increased concentrations of oxygen-containing groups on double-walled or multiwalled CNTs [63,64] and graphite [65] actually slow the rate of heterogeneous electron transfer. In fact, Pumera et al [66] consider that oxygen-containing groups play a minor role in heterogeneous electron transfer for electrochemically activated MWNTs, and suggest instead that the increased heterogeneous electron-transfer rate lies in an increase of the density of edge-like sites on the sidewalls of the tubes.…”
mentioning
confidence: 92%